Molecular photofragment orientation in the photodissociation of H2O2 at 193 nm and 248 nm. - Chang, Y; Brouard, M; Cireasa, R; Perkins, T; Seamons, SA (2011)
Angular momentum orientation has been observed in the OH(X(2)Π, v = 0) fragments generated by circularly polarized photodissociation of H(2)O(2) at 193 nm and 248 nm. The magnitude and sign of the orientation are strongly dependent on the OH(X) photofragment rotational state. In addition to conventional laser induced fluorescence methods, Zeeman quantum beat spectroscopy has also been used as a complementary tool to probe the angular momentum orientation parameters. The measured orientation at 193 nm is attributed solely to photodissociation via the Ã(1)A state, even though at this wavelength H(2)O(2) is excited near equally to both the Ã(1)A and B(1)B electronic states. This observation is confirmed by measurements of the photofragment orientation at 248 nm, where access to the Ã(1)A state dominates. Several possible mechanisms are discussed to explain the observed photofragment orientation, and a simple physical model is developed, which includes the effects of the polarization of the parent molecular rotation upon absorption of circularly polarized light. Good agreement between the experimental and simulation results is obtained, lending support to the validity of the model. It is proposed that photofragment orientation arises mainly from the coupling of the parent rotational angular momentum with that induced during photofragmentation.